Do studies reporting 'U'-shaped serum 25-hydroxyvitamin D–health outcome relationships reflect adverse effects?. Issue 1 (1st January 2016) - Grant, William B.; Karras, Spyridon N.; Bischoff-Ferrari, Heike A.; Annweiler, Cedric; Boucher, Barbara J.; Juzeniene, Asta; Garland, Cedric F.; Holick, Michael F.
ABSTRACT: Several reports describe U-shaped 25-hydroxyvitamin D [25(OH)D] concentration–health outcomes, including musculo-skeletal disorders such as falls and fractures, several cancers, cardiovascular disease (CVD), cognitive function, all-cause mortality rates, birth outcomes, allergic reactions, frailty, and some other disorders. This paper reviews reports of U-shaped outcome associations with vitamin D status for evidence of underlying pathophysiological processes, or of confounding, finding that some U-shaped associations appear to be biologically meaningful, but that many could well reflect confounding by factors such as lifestyle, or hypovitaminosis D-related disease onset being masked by self-supplementation that was begun too late to correct developing health problems but before baseline vitamin D status assessment. However, the various U-shaped associations for allergic reactions may be due to vitamin D modulation of the phenotype of the immune response, shifting the Th1-Th2 balance toward Th2 formation. For prostate cancer, there seems to be little effect of 25(OH)D concentration on incidence; however, there is an inverse correlation between 25(OH)D concentration and mortality rates. Future observational studies, and randomized controlled trial data analyses, should include adjustment for data collected on prior long-term vitamin D supplementation and solar UVB exposure, as well as other potential confounders.